Study of the Carrier State for Five BRCA1/BRCA2 Deleterious Mutations in Bulgarian Women with Breast Cancer - Katia Kovacheva; Zornica Kamburova; Savelina Popovska; Ivan Ivanov; Maria Simeonova; Petia Angelova (Journal of Biomedical & Clinical Research)
Genetic testing for BRCA 1/2 mutation is a well recognized medical management tool. Identification of healthy carriers of such mutations allows effective risk reduction procedures to be performed. There is no data reported on the founder mutations in the Bulgarian population. To evaluate the contribution of genetic factors to breast cancer (BC), we investigated the carrier state of Bulgarian women with BC for five common (according to BIC database) deleterious BRCA1/2 mutations. The list of patients diagnosed with BC between January 2011 and April 2012 was obtained from the Cancer Registry of University Hospital, Pleven. Eighty-two women with BC were interviewed and a pedigree was constructed of each of them. The patients were classified into seven categories, according to personal, disease and family history. Based on the preliminary prepared selection criteria and the personal family history, we defined a target group of 33 Bulgarian women with BC. They were screened for five deleterious mutations: 5382insC in BRCA1 and 6174delT, 6079del4, 8138del5, 5946delCT in BRCA2, by DNA sequencing. The genetic analysis detected none of the tested mutations. Two polymorphic variants were found in BRCA2 gene: c.5744C>T (rs4987117, SNP database) in exonl 1E in one patient and c.7806-14T>C (rs9534262, SNP database) in exonl7 in 22 patients. In conclusion, without basic information on the founder mutations in the population, the genetic screening for the specific mutations in a small group of tested patients is ineffective.